Pelaksanaan Gotong Royong di Era Globalisasi (Studi Kasus di Desa Bah Tobu Kecamatan Dolok Batu Nanggar Kabupaten Simalungun) - Putri Widia Ningsih; Dewi Romantika Tinambunan; Aulia Azzahra; Sri Yunita (Journal on Education, 2023)
This research examines gotong royong as a tradition in the village of Bah Tobu where the people have ethnic and religious diversity. Gotong royong is still being carried out intensively because it can maintain harmony between residents. The purpose of this research is to find out the existence and implementation of gotong royong in the village of Bah Tobu. The method used in this study uses a qualitative approach with a case study research design. The results of this study are that the implementation of mutual cooperation in the village of Bah Tobu is going well through collaboration between residents and the village government. Mutual cooperation in the village of Bah Tobu is divided into There are two forms, namely inter-religious cooperation and intra-religious mutual cooperation. In intra-religious mutual cooperation which is carried out only within members of one religion, namely in the social sector such as cleaning and building houses of worship as well as religious activities and also in the economic field including raising funds for events religious celebrations. While Inter-religious Activities are carried out in two fields, namely the economic and social fields by all villagers regardless of religious differences which are carried out in the social sector, namely environmental hygiene and an event organized by the village government while in the economic field, namely collecting funds for village development or activities held in the village. The conclusion from this research is not all mutual cooperation can be carried out by all residents, but there is also mutual cooperation which is only carried out based on the scope of religion. Then in mutual cooperation in Bah Tobu village there are those who use elements of coercion and also voluntarily. The element of coercion in question is if a citizen does not take part in a mutual cooperation activity, he will be subject to sanctions in the form of fines.